Facile synthesis of fusiform layered oxides assisted by microwave as cathode material for lithium-ion batteries. (November 2017) - Huang, Zhixiong; Zhou, Yujia; Liu, Yingying; Liu, Qiang; Hua, Xiaoyan; Shi, Shaojun; Zuo, Mingming
Graphical abstract: Fusiform layered oxides synthesized by microwave solvothermal reaction with excellent electrochemical property as cathode material for lithium-ion batteries. Highlights: LiMn0.25 Ni0.5 Co0.25 O2 is obtained by microwave solvothermal reaction. Material synthesized at 800 °C exhibits fusiform hierarchical morphology. High initial discharge capacity of 183 mAh g −1 is reached at 0.1C. 154 mAh g −1 is remained with a capacity retention of 84.2% after 100 cycles. Excellent rate capability is also obtained. Abstract: A facile microwave solvothermal reaction is performed to synthesize novel LiMn0.25 Ni0.5 Co0.25 O2 ternary layered oxide with 1 D fusiform morphology. Scanning electron microscopy (SEM) images show that material synthesized at 800 °C well keeps the fusiform morphology of the precursor with a particle size of 100–300 nm. All the three elements are perfectly dispersed and a well-formed layered structure is obtained. Thus, good electrochemical performances with high initial discharge capacity of 183 mAh g −1 is reached. Furthermore, high discharge capacity of 154 mAh g −1 is remained with a capacity retention of 84.2% after 100 cycles at 20 mA g −1 . Excellent rate capability is also obtained with high discharge capacity of 99 mAh g −1 at 2000 mA g −1 . It seems such facile microwave solvothermal method is one of the most promising candidates for preparing ternary layered oxides with excellent electrochemical properties as cathode material for lithium ion batteries.